2017
DOI: 10.1097/acm.0000000000001141
|View full text |Cite
|
Sign up to set email alerts
|

Building a Framework of Entrustable Professional Activities, Supported by Competencies and Milestones, to Bridge the Educational Continuum

Abstract: The transition to competency-based medical education (CBME) and adoption of the foundational domains of competence by the Accreditation Council for Graduate Medical Education, Association of American Medical Colleges (AAMC), and American Board of Medical Specialties' certification and maintenance of certification (MOC) programs provided an unprecedented opportunity for the pediatrics community to create a model of learning and assessment across the continuum. Two frameworks for assessment in CBME have been pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
160
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(166 citation statements)
references
References 25 publications
0
160
0
6
Order By: Relevance
“…29,30 EPA descriptors for each level of supervision could be described to standardize entrustment decisions. 27 Milestones could be helpful to drill down where trainees are struggling to facilitate appropriate remediation.…”
Section: Relationship To Other Variables: How Do Results From Milestomentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 EPA descriptors for each level of supervision could be described to standardize entrustment decisions. 27 Milestones could be helpful to drill down where trainees are struggling to facilitate appropriate remediation.…”
Section: Relationship To Other Variables: How Do Results From Milestomentioning
confidence: 99%
“…[26][27][28] EPAs could be mapped to milestones and, along with research, determine whether they were mapped correctly. Each rotation could then assess a limited number of EPAs along supervisory lines, as suggested by Rekman and colleagues' Ottawa Clinic Assessment Tool.…”
Section: Relationship To Other Variables: How Do Results From Milestomentioning
confidence: 99%
“…As a consequence, tensions may surface through differing, ambiguous and sometimes conflicting assessment strategies such as the ‘standardisation’ of inherently unstandardised assessments (e.g. standardised narratives for authentic assessments), ‘measurement’ of performance‐in‐context through the use of detailed rating scales and task‐specific checklists, or the ‘objectification’ of competence and competence development through the use of entrustable professional activities and milestones …”
Section: Polarities and Tensions In Assessment: Categorisation And Dementioning
confidence: 99%
“…standardised narratives for authentic assessments), 57,58 'measurement' of performance-in-context through the use of detailed rating scales and task-specific checklists, 59,60 or the 'objectification' of competence and competence development through the use of entrustable professional activities and milestones. 61,62 In addition, education accountability may entail a 'timekeeping function' of assessment as assessment may (implicitly or explicitly) serve to increase the rate of learning: frequent assessments become 'stopwatches', controlling individual progress and the efficiency of learning processes. 63 Tensions between control and trust, or between standardisation and authenticity may then not only interfere with processes of teaching and learning in classroom settings or work environments, 64-68 but also impact on stakeholders' sense of autonomy, agency and engagement with assessment as a tool for learning.…”
Section: Cost-effectiveness Learning/educating and Performingmentioning
confidence: 99%
“…Some of the contributions that come from this area are: the transition to competency-based medical education, through the entrustable professional activities (EPAs) in order to reduce the gap between theory and practice (ten Cate, & Scheele, 2007;Carraccio et al, 2017); a systematic research of the scientific literature (Greenfield, & Braithwaite, 2008) found that the accreditation programs lead to development of health professionals; or 'the opportunity for residents to learn in innovative programs, and enhanced resident education in quality, patient safety, and the new competencies' (Nasca, Philibert, Brigham, & Flynn, 2012, p. 1055) with the introduction of the Next Accreditation System (NAS) by the Accreditation Council for Graduate Medical Education (ACGME).…”
Section: Rpl Professional Certificates and Social Justicementioning
confidence: 99%